2004
DOI: 10.1161/01.cir.0000105764.22626.b1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Systemic Nitric Oxide Synthase Inhibition With Asymmetrical Dimethylarginine in Humans

Abstract: Background— Increased blood concentrations of the endogenous nitric oxide synthase (NOS) inhibitor asymmetrical dimethylarginine (ADMA) have been linked to excess cardiovascular morbidity and mortality and to progression of renal disease. We evaluated systemic cardiovascular effects of ADMA infusion in healthy subjects using invasive techniques, ie, right heart catheter and inulin/para-aminohippurate clearance. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
241
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(261 citation statements)
references
References 41 publications
12
241
0
8
Order By: Relevance
“…In previous studies in patients with CKD we found that high ADMA and high FGF-23 were associated with altered endothelium-dependent response to forearm ischemia. 16,26 These studies showed that high ADMA is associated with an important attenuation of the link between FGF-23 and endotheliumdependent vasodilatation, suggesting that these factors may share a common pathway disturbing endothelial function in CKD. 26 These observations, along with previous studies linking these two biomarkers with CKD progression, formed a strong a priori hypothesis for modeling the combined effect of FGF-23 and ADMA on the risk for progression to kidney failure in the first cohort of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies in patients with CKD we found that high ADMA and high FGF-23 were associated with altered endothelium-dependent response to forearm ischemia. 16,26 These studies showed that high ADMA is associated with an important attenuation of the link between FGF-23 and endotheliumdependent vasodilatation, suggesting that these factors may share a common pathway disturbing endothelial function in CKD. 26 These observations, along with previous studies linking these two biomarkers with CKD progression, formed a strong a priori hypothesis for modeling the combined effect of FGF-23 and ADMA on the risk for progression to kidney failure in the first cohort of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide (NO) synthase and a modulator of cardiovascular 16 and renal 17 function, has been reported to be a risk factor for endothelial dysfunction 18 and atherosclerosis 19 associated with progression of CKD in several cohort studies. [20][21][22][23] Experimental data show that ADMA administration in uninephrectomized mice induced glomerular and vascular fibrosis, with elevated deposits of collagen I, III, and fibronectin, as well as reduced peritubular capillaries.…”
mentioning
confidence: 99%
“…Intravenously administered ADMA acutely increases systemic vascular resistance (SVR) and BP in humans and animals. [11][12][13] Thus, in SS but not SR blacks, an increased formation of ADMA induced by NaCl loading might render pressor its normal transient increase of CO by inhibiting an otherwise offsetting vasodilatation, as judged by that induced in the SR subjects. We report observations supporting this hypothesis.…”
mentioning
confidence: 99%
“…Thus, it is plausible Fibroblast growth Factor-23: a novel biomarker For cardiovascular disease ... that some of the effects of FGF-23 on the cardiovascular system are at least partly mediated through suppression on active vitamin D. Moreover, FGF-23 may also induce endothelial dysfunction by directly interfering with nitric oxide (NO)-mediated vasodilation. Asymmetric dimethylarginine (ADMA), the most abundant endogenous inhibitor of NO synthase, has been reported to be a risk factor for endothelial dysfunction and atherosclerosis [56][57][58]. An experimental study demonstrated that FGF-23 increase superoxide levels in endothelial cells and aortic rings, inhibits nitic oxide bioavailability and causes endothelial dysfunction in mouse aorta [59].…”
Section: Fibroblast Growth Factor-23 and Other Ckd-related Cardiovascmentioning
confidence: 99%